2021
DOI: 10.3390/ijms22094507
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Isl1 under the Pax2 Promoter, Leads to Impaired Sound Processing and Increased Inhibition in the Inferior Colliculus

Abstract: The LIM homeodomain transcription factor ISL1 is essential for the different aspects of neuronal development and maintenance. In order to study the role of ISL1 in the auditory system, we generated a transgenic mouse (Tg) expressing Isl1 under the Pax2 promoter control. We previously reported a progressive age-related decline in hearing and abnormalities in the inner ear, medial olivocochlear system, and auditory midbrain of these Tg mice. In this study, we investigated how Isl1 overexpression affects sound pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…During inner ear development, ISL1 is expressed in both neuronal and sensory precursors ( 19 , 21 , 22 ). Transgenic modulations of Isl1 indicate important roles of ISL1 in the maintenance and function of neurons and hair cells and as a possible contributing factor in neurodegeneration ( 64 67 ). These studies suggest that ISL1 plays a role in developing neurons and sensory cells, but no direct evaluation of ISL1 function has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…During inner ear development, ISL1 is expressed in both neuronal and sensory precursors ( 19 , 21 , 22 ). Transgenic modulations of Isl1 indicate important roles of ISL1 in the maintenance and function of neurons and hair cells and as a possible contributing factor in neurodegeneration ( 64 67 ). These studies suggest that ISL1 plays a role in developing neurons and sensory cells, but no direct evaluation of ISL1 function has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…During inner ear development, ISL1 is expressed in both neuronal and sensory precursors 18, 20, 21, 22, 75 . Transgenic modulations of Isl1 indicate important roles of ISL1 in the maintenance and function of neurons and hair cells and as a possible contributing factor in neurodegeneration 23, 76, 77, 78 . These studies suggest that ISL1 plays a role in developing neurons and sensory cells, but no direct evaluation of ISL1 function has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that Isl1 Cre -mediated Neurod1 deletion ( Neurod1CKO ) results in a disorganized cochleotopic projection from SGNs 18 , affecting acoustic information processing in the central auditory system of adult mice at the physiological and behavioral levels 19 . During inner ear development, ISL1 is expressed in the differentiating neurons and sensory precursors 18, 20, 21, 22, 23 . Isl1 is expressed in all four populations of SGNs (type Ia, Ib, Ic, and type II) identified by single-cell RNA sequencing 4 .…”
Section: Introductionmentioning
confidence: 99%